Effect of Level of Dietary Protein and Addition of Probiotic on rumen Fermentation Characteristics in Awassi Lambs (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This study was conducted in the Animal field of Animal Production Department-College of Agriculture- Al-Qasim Green University to investigate the effect of utilization of two levels of dietary crude protein (CP), 12.5 and 14.5% with or without addition of  BioSB-Gold probiotic (P) into concentrate diet at rate of 1 kg/ton on rumen fermentation characteristics in Awassi lambs.Sixteen male Awassi lambs with average weight of 18.76 ± 3.34 and age of 4-6 months were used. Lambs were randomly allocated into individual pens at rate of 4lambs per each treatments. Concentrate diets were offered at 2.5% of live body weight with two meals, at morning and evening. Wheat straw was offered ad libitum. Samples of rumen liquid were withdrawn from all animals before feeding and 3 and 6 hours later. Results revealed that increasing CP levels from 12.5 th 14.5% did not affect pH values significantly but it resulted in a significant increase(P